Peningkatan Kapasitas Guru dalam Merancang Pembelajaran Mendalam Melalui Pelatihan Pemanfaatan Board Game di SMPN 49 Maluku Tengah - Latuheru, Henry; Monica, Monica; Bilmona, Hanafi; Ferdinandus, Marcy; Lekatompessy, Felicia Miranda; Lewier, Christian Albert (Civiliza Publishing, 2025)
The implementation of the Independent Curriculum requires teachers to create innovative and interactive learning processes, but the limitations of interesting media and strategies are often a challenge, especially in areas with limited access. This service activity aims to increase the professional capacity of 30 teachers from SMPN 49 and SMPN 53 Central Maluku in integrating board games as an effective learning medium and supporting the creation of Deep Learning. The method of implementing the activity is centralized training (hands-on workshop) and subject group assistance which is carried out for 1 day with a total duration of 3 hours. This training focused on sample board game analysis (My Favorite and Word Brick) and a prototype design mini-workshop by seven subject groups. The results of the evaluation showed a very satisfactory level of participant satisfaction with an average score of 3.75 out of a scale of 4.0, indicating that the applicable training method was in accordance with the needs of the teacher. In addition, 85% of participants stated that there was a significant increase in knowledge and self-efficacy on the potential of board games as a teaching medium. The concrete output produced is 7 board game prototypes that are ready to be implemented. The main benefit obtained is the diversification of teachers' learning strategies. In conclusion, this training successfully equips teachers with new skills in designing effective interactive media and makes a significant contribution to improving the quality of teaching at partner schools.